The intrathecal, polyspecific antiviral immune response in neurosarcoidosis, acute disseminated encephalomyelitis and autoimmune encephalitis compared to multiple sclerosis in a tertiary hospital cohort. Issue 1 (December 2015) - Hottenrott, Tilman; Dersch, Rick; Berger, Benjamin; Rauer, Sebastian; Eckenweiler, Matthias; Huzly, Daniela; Stich, Oliver
Abstract Background A polyspecific, intrathecal humoral immune response against the neurotropic viruses, measles, rubella and varicella zoster virus, called "MRZ reaction" (MRZR), is present in the majority of patients with multiple sclerosis (MS). Neurosarcoidosis (NS) and acute disseminated encephalomyelitis (ADEM) are important clinical differential diagnoses of MS. Autoimmune encephalitis (AIE) represents a well characterized autoimmune CNS disorder with intrathecal antibody synthesis. The aim of this study was to investigate the specificity of MRZR for MS in patients with NS, ADEM and AIE for the first time, and to compare it with the diagnostic value of oligoclonal bands (OCB). Patients and methods Twenty-two patients with NS, 17 with AIE, 8 with ADEM and 33 with MS serving as controls were analyzed for OCB and MRZR by calculation of the antibody index (AI) for each virus. MRZR was considered as positive if at least two AIs were ≥1.5. Results A positive MRZR was statistically significantly less frequent in NS (9 %), AIE (11 %) and ADEM (0 %) compared to MS patients (70 %;p  < 0.001 each). The specificity of MRZR for MS was 92 % in the study cohort. In comparison to MRZR, the OCB showed a higher sensitivity (100 %), but a lower specificity (69 %) for MS. Conclusion These results indicate that MRZR seems to be the most specific available CSF marker of MS.